Scholarship, Blogging, and Tradeoffs: On Discovering, Disseminating, and Doing - Eugene Volokh (Washington University Law Review, 2006)
Now, more than ever before, we legal academics have to, at least in some measure, choose. Should we spend the bulk of our time discovering, with the reputational, professional, and emotional benefits that this produces? Or should we spend more of the time disseminating, mostly disseminating views that are our own but are based on others’ discoveries, with the very different reputational, professional, and emotional benefits that this produces? Sure, it’s our choice, at least once we have tenure. But how should we exercise that choice? Yes, we’re probably better off both discovering and disseminating, if we’re good at both and enjoy both. But how much of both?
Keywords: Blogs; Law – Study & amp; teaching; Legal literature; Legal publishing; United States